Femtosecond laser cleaning for aerospace manufacturing and remanufacturing - Maharjan, Niroj (2018)
Microsecond and nanosecond lasers have been studied in the past for laser cleaning applications, but femtosecond laser is rarely used for cleaning due to the greater possibility of ablation from the extremely high peak power (in gigawatt range) of ultrashort pulses. This paper reports the investigation into the feasibility of using femtosecond laser as a tool for surface cleaning of aerospace components. Surface contaminants, oxides and surface coatings were shown to be removed effectively and damage to the substrate was avoided by using a defocused laser beam and careful control of laser fluence.